2003
DOI: 10.1046/j.1523-1747.2003.12600.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 15 Promoter Targets Putative Epithelial Stem Cells in the Hair Follicle Bulge

Abstract: Putative epithelial stem cells in the hair follicle bulge are thought to play pivotal roles in the homeostasis, aging, and carcinogenesis of the cutaneous epithelium. Elucidating the role of bulge cells in these processes has been hampered by the lack of gene promoters that target this area with specificity. Here we describe the isolation of the mouse keratin 15 (K15) promoter and demonstrate its utility for preferentially targeting hair follicle bulge cells in adult K15/lacZ transgenic mice. We found that pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
275
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(300 citation statements)
references
References 46 publications
23
275
0
2
Order By: Relevance
“…and 19 and ␣ 6-integrin, which are markers of epithelial stem cells ( Liu et al, 2003;Blanpain and Fuchs, 2006 ). In all cases, and in agreement with the LRC-based experiments, we observed an increased immunoreactive signal in the bulge region from Zmpste24 -null mice ( Fig.…”
Section: Introductionsupporting
confidence: 90%
“…and 19 and ␣ 6-integrin, which are markers of epithelial stem cells ( Liu et al, 2003;Blanpain and Fuchs, 2006 ). In all cases, and in agreement with the LRC-based experiments, we observed an increased immunoreactive signal in the bulge region from Zmpste24 -null mice ( Fig.…”
Section: Introductionsupporting
confidence: 90%
“…K15 staining has been shown to highlight the bulge area. 31,41 Rare Oct4-positive cells can be seen in the epidermis as previously described 40 ; however, most of the Oct4-positive cells in skin were located in the hair follicles within the area highlighted by K15 staining in both anagen and catagen/telogen hair follicles ( Figure 6A). We then performed immunostaining on plucked human hair follicles after they were cultured in hESC medium for 6 days.…”
Section: Oct4-positive Cells Are Located In the Bulgesupporting
confidence: 61%
“…12,26 In humans, however, the biological properties of K15 þ cells have not been fully examined because viable human K15 þ cells cannot be purified by cell sorting due to the membrane permeabilization required for staining intracellular cytokeratins. On the other hand, CD200 þ cells can be purified; thus we sorted CD200 þ CD34 -and CD34 þ populations from isolated follicular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among many reports that described various biomarkers for identifying hair follicle stem cells, 4-11 the most convincing evidence was provided in recent reports suggesting that K15 and CD200 are biomarkers for human follicular stem cells that reside in the bulge. 9,11,12 It had previously been shown that human and murine bulge cells specifically expressed K15. 9 Skin and hair follicle analyses in K15/LacZ transgenic mice showed that K15 promoter activity was correlated with the differentiation level of epidermal and follicular keratinocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation